Strategies to support the caregiver of people with cancer: integrative review - Ramos, Diego Henrique Silveira; Mendonça, Erica Toledo de; Pedretti, Pedro Alexandre Henriques; Lins, Ana Luiza Rodrigues; Andrade, João Vitor (Revista de Medicina, 2022)
Objective: conduct an integrative literature review about which care and support strategies are offered to the caregiver of people with cancer, in the hospital, outpatient and or home environment. Method: integrative literature review in the electronic databases BDENF, LILACS, MEDLINE, Portal CAPES, PubMed and SciELO, through the descriptors “Family Therapy”, “Family Nursing”, “Caregivers”, “Neoplasms”, “Integral Health Care” in Portuguese, English and Spanish. The Boolean operators “OR” and “AND” were used to cross the descriptors. Results: after careful review, 7 articles met the inclusion criteria. Strategies such as training for physical care and symptom management, stimulating the development of self-efficacy, coping and self-care skills through the provision of information and psychoeducational interventions, physical activities, use of complementary integrative practices and also the approximation of family ties as promoters of reducing overload and feelings of incapacity. Conclusion: the studies emphasized several support strategies that promote the reduction of overload and feelings of incapacity. Further studies are needed to validate some of the results that have not been proven to have a significant impact on caregivers’ quality of life.